Bilingval leksikografi - Nederlandsk-dansk ordbogsprojekt - Laureys, Godelieve; Rawoens, Gudrun (Nordiske Studier i Leksikografi, 2001)
In I 997 the Department of Nordic languages of Ghent University started up a Dutch-Danish dictionary project. The aim is to create a bilingual database of about 40.000 lemmas. The commissioner of the project is the CL VV ("Committee for lexicographical interlingual resources"), a Dutch-Belgian official agency that coordinates bilingual dictionary projects with Dutch as one of the involved languages. A Dutch-Danish bilingual lexical database is produced by means of the editor OMBI with a reverse function as one of its key features. RBN ("Referentiebestand Nederlands"), a corpus based predictionary lexical database, forms our material for the source language. In this article we intend to present this project by describing our way of working with the OMBI-program (network, advantages, problems) and with the RBN-material (macro, micro). A few editorial matters will be highlighted and illustrated with examples.